Of Shepherds, Sheep, and the Cross-autocorrelations in Equity Returns - Badrinath, S.G.; Kale, Jayant R.; Noe, Thomas H. (Review of Financial Studies, 1995)
We present an economic mechanism and supportive empirical evidence for the transmission of information between equity securities first documented by Lo and MacKinlay (1990). It is argued that the past returns on stocks held by informed institutional traders will be positively correlated with the contemporaneous returns on stocks held by noninstitutional uninformed traders. Evidence consistent with this hypothesis is then presented. We document that the returns on the portfolio of stocks with the highest level of institutional ownership lead the returns on portfolios of stocks with lower levels of institutional ownership. This effect persists even after firm size is controlled for and is apparent at longer lags than the size-related lag effects documented in Lo and MacKinlay (1990).